Pengaruh kompetensi, insentif dan pengalaman kerja terhadap kinerja karyawan di Lampung - Adjie Hermawan; Amelia Wulandari; Andini Mirza Buana; Vicky Sanjaya (Studi Ilmu Manajemen dan Organisasi, 2020)
Purpose: This study aimed at examining the effect of competence, incentives and work experience on employee performance. Research methodology: A quantitative approach was the method used for this analysis. The research was performed by a total of 47 workers in Lampung. The PLS-based structural equation modeling has been used to perform statistical experiments. The validation test used the load value of the factor, while the reliability test used the alpha, the composite and the average variance of the Cronbach (AVE). Results: From the results of hypothesis testing, there is a conclusion that competence has a positive effect on employee performance with a P-Value (0.015 <0.05), the incentive variable shows a P-Value (0.758> 0.05), meaning that hypothesis 2 is rejected and the work experience variable shows that experience Work has a positive and insignificant effect on employee performance with a P-Value (0.183> 0.05), so hypothesis 3 is accepted. Limitation: There was limited time in conducting the research. Contribution: This study contributes to disseminate information regarding competence and work experience that need to be developed so that employees can improve their performance at work. Keywords: Competence, Incentives, Work experience, Employee performance